Living nature and the (im)possibility of the word: an approach to Carlos Oquendo de Amat’s poem «mother» - Pajuelo Milla, Gloria María (2023)
Our reading suggests that the poem «mother», by Carlos Oquendo de Amat, exposes a retrospective vision of the speaker, as if he were retreating to an idealised, childlike and happy past in which the mother figure offered him protection, affection, security and taught him to speak. Through similes and metaphors, it is argued that the mother shares characteristics with living nature, but her absence in the present time affects the speaker; therefore, he resorts to the word to make up for this affective and communicative lack, but he is confronted with the (im)possibility of verbal language.